COMBINATION THERAPY WITH ATENOLOL AND AMLODIPINE AND CORRECTION OF CARDIOVASCULAR AUTONOMIC DYSFUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION - A. R. Kiselev; V. I. Gridnev; A. S. Karavaev; O. M. Posnenkova; V. A. Shvartz; V. I. Ponomarenko; M. D. Prokhorov; B. P. Bezruchko (Российский кардиологический журнал, 2012)
Aim. To assess the effects of the combination therapy with atenolol and amlodipine on the synchronisation of 0,1-Hz rhythms of heart rate variability (HRV) and distal vessel filling (DVF). Material and methods. The study included 25 patients with Stage 1–2 arterial hypertension (AH), aged 58±8 years. The registration of 0,1-Hz oscillations in HRV and DVF was performed during the passive tilt test with spontaneous breathing; each test stage lasted for 10 minutes. Synchronisation was assessed by the phase difference between 0.1 Hz-rhythms in HRV and DVF. Frequency values of the HRV spectrum in LF and HF-ranges were also assessed. The duration of combination therapy was 8 weeks. Results. In patients with AH and a markedly manifested autonomic dysfunction, the therapy with atenolol and amlodipine was associated with some improvement in the functional interaction between HRV and DVF 0,1-Hz rhythms. In the rest of AH patients, the treatment was linked to stable levels of cardiac 0,1-Hz regulation and slightly decreased synchronisation levels. All participants demonstrated an increase in the influence of respiratory parasympathetic effects. Conclusion. The combination therapy with atenolol and amlodipine effectively corrected autonomic cardiovascular dysfunction in patients with Stage 1–2 AH.